Anti-infective vaccination strategies in patients with hematologic malignancies or solid tumors—Guideline of the Infectious Diseases Working Party (AGIHO) of the German Society for Hematology and Medical Oncology (DGHO). (24th April 2018) - Rieger, C T; Liss, B; Mellinghoff, S; Buchheidt, D; Cornely, O A; Egerer, G; Heinz, W J; Hentrich, M; Maschmeyer, G; Mayer, K; Sandherr, M; Silling, G; et al.
Abstract: Infectious complications are a significant cause of morbidity and mortality in patients with malignancies specifically when receiving anticancer treatments. Prevention of infection through vaccines is an important aspect of clinical care of cancer patients. Immunocompromising effects of the underlying disease as well as of antineoplastic therapies need to be considered when devising vaccination strategies. This guideline provides clinical recommendations on vaccine use in cancer patients including autologous stem cell transplant recipients, while allogeneic stem cell transplantation is subject of a separate guideline. The document was prepared by the Infectious Diseases Working Party (AGIHO) of the German Society for Hematology and Medical Oncology (DGHO) by reviewing currently available data and applying evidence-based medicine criteria.